Effective fractionation of lignocellulose components and lignin valorization by combination of deep eutectic solvent with ethanol - Cui, Pingping; Ye, Zhishang; Chai, Mengzhen; Yuan, Jie; Xiong, Yan; Yang, Haitao; Yao, Lan (Frontiers in Bioengineering and Biotechnology, 2023)
A combination of deep eutectic solvent with ethanol was developed for pretreatment of Broussonetia papyrifera to effectively extract lignin and promote the subsequent enzymatic hydrolysis. In order to further explore the optimal conditions for enzymatic hydrolysis, a central composite design method was applied. The correlation between each factor and glucose yield was obtained, and the optimal conditions was 160 °C, 60 min, DES/E=1/1(mol/mol). The results showed that compared with control, the glucose yield increased by 130.67% under the optimal pretreatment conditions. Furthermore, the specific surface area of biomass was increased by 66.95%, and the content of xylan and lignin was decreased by 86.71% and 85.83%. The correlation between xylan/lignin removal and enzymatic hydrolysis showed that the removal of lignin facilitated the glucose yield more significantly than that of xylan. To further explore the lignin valorization, the structural and antioxidant analysis of recovered lignin revealed that high temperature was favorable for lignin with good antioxidant performance. This pretreatment is a promising method for separating lignin with high antioxidant activity and improving cellulose digestibility.